Eclosión, muerte embrionaria y crecimiento de pollitos en gallinas doble propósito y de riña bajo condiciones hipobáricas naturales. - Paredes, M (2021)
The present study aimed to compare results for hatchability and growing performance of chicks from 2 biotypes, dual purpose (DP) and brawl (BR), in hipobaric conditions (2718 m above sea level). In experiment 1, a total of 352 hatching eggs were randomly arranged, 176 egg of DP y 176 BR. In experiment 2, a total of 114 one-day-old unsexed chickens were reared for 28 d. The experimental design for hatchability and chick performance variables was completely randomized with 2 treatments (DP and BR). There were no differences between the studied treatments for hatchability results (p>0.05). Hens’ biotype affected chicken performance in the rearing phase (p<0.01), where the DP chickens had better body weight and feed conversion than BR, but BR chickens had lower mortality than DP chickens.